International Portfolio Diversification Opportunities for the Indian Investors in and Around U.S. 2007-09 Financial Crisis : An ARDL Application for Future Reference - Dasgupta, Ranjan (Indian Journal of Finance, 2017)
This study primarily aimed at finding the portfolio diversification and arbitrage opportunities for the Indian and international investors by investigating the short- and long-run associations and co-integrations in between the Indian and 40 international stock markets amidst the recent U.S. financial crisis overall and under selected structural breaks. To fulfill its objectives, this study used the most advanced autoregressive distributed lag on transformed natural log returns of these countries' benchmark indices monthly closing values. This was conducted by estimating regression equations by ordinary least squares and subsequent F or Wald test, then after establishing co-integrations, it estimated conditional ARDL, and lastly obtained the short-run dynamic adjustments by estimating an error correction model. Long-run co-integration results showed that there were enough portfolio diversification opportunities for the Indian investors in Asian and Latin American markets in the overall study period. However, during the crisis period, both Indian and international investors had less number of profitable diversification opportunities as most of these international stock markets were co-integrated. In the short-run, these markets showed dynamic adjustments, especially in the post-crisis period, generally within one month, which neutralized the arbitrage opportunities. These findings will have important implications for the formulation of policies of multinational corporations working in these countries in regard to their capital budgeting decisions, treasury management activities, and forex transactions. The data provided in the paper will be indispensable for international managers to mitigate international risks in terms of transactions and translations. Implications of the U.S. crisis on co-integrating relationships and efficiency of these markets will also be helpful to policymakers and other stakeholders in this area.